Model Kepemimpinan Digital Kepala Sekolah di Era Teknologi - Zubaidah Zubaidah; Rahmad Syah Putra (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Currently, transformation has occurred so quickly, the Industrial Revolution Era was one of the eras of very rapid technological development. With the rapid development of technology, various knowledge, new skills, and new leadership have been born in realizing the competitiveness of an educational institution. This article aims to describe the leadership of school principals in the technological era. The writing of this article uses a qualitative descriptive approach (library research), by conducting a careful review of some material and leadership theory. The results of the study show that: 1) a leader or leaders in the technological era in order to bring a team to a better realm, must master 10 (ten) skill models namely complex problem solving, critical thinking, creativity, management ability, coordination, emotional intelligence , making policies/decisions, service orientation, negotiation, and cognitive flexibility; 2) There are digital leadership characteristics that exist in a school principal in the Technology Age, including: responsibility and innovation in order to direct the organization to transform towards digital; 3) The implementation of digital leadership in educational institutions, of course, must be carried out by a Principal with several stages, namely: The emerging, implementing, instilling and transforming stages, and 4C, namely; critical in thinking and able to generate solutions, communication, collaborative, as well as creative and innovative.